Combination effects of peramivir and favipiravir against oseltamivir-resistant 2009 pandemic influenza A(H1N1) infection in mice. - Sehee Park; Jin Il Kim; Ilseob Lee; Sangmoo Lee; Min-Woong Hwang; Joon-Yong Bae; Jun Heo; Donghwan Kim; Seok-Il Jang; Hyejin Kim; Hee Jin Cheong; Jin-Won Song; et al. (PLoS ONE, 2014)
Antiviral drugs are being used for therapeutic purposes against influenza illness in humans. However, antiviral-resistant variants often nullify the effectiveness of antivirals. Combined medications, as seen in the treatment of cancers and other infectious diseases, have been suggested as an option for the control of antiviral-resistant influenza viruses. Here, we evaluated the therapeutic value of combination therapy against oseltamivir-resistant 2009 pandemic influenza H1N1 virus infection in DBA/2 mice. Mice were treated for five days with favipiravir and peramivir starting 4 hours after lethal challenge. Compared with either monotherapy, combination therapy saved more mice from viral lethality and resulted in increased antiviral efficacy in the lungs of infected mice. Furthermore, the synergism between the two antivirals, which was consistent with the survival outcomes of combination therapy, indicated that favipiravir could serve as a critical agent of combination therapy for the control of oseltamivir-resistant strains. Our results provide new insight into the feasibility of favipiravir in combination therapy against oseltamivir-resistant influenza virus infection.